One-step 18F-labeling of peptides for positron emission tomography imaging using the SiFA methodology - Wängler, Carmen; Niedermoser, Sabrina; Wängler, Björn (Nature protocols, 2012)
Here we present a procedure to label peptides with the positron-emitting radioisotope fluorine-18 (18F) using the silicon-fluoride acceptor (SiFA) labeling methodology. Positron emission tomography (PET) has gained high importance in noninvasive imaging of various diseases over the past decades, and thus new specific imaging probes for PET imaging, especially those labeled with 18F, because of the advantageous properties of this nuclide, are highly sought after. N-terminally SiFA-modified peptides can be labeled with 18F− in one step at room temperature (20-25 °C) or below without forming side products, thereby producing satisfactory radiochemical yields of 46 ± 1.5% (n = 10). The degree of chemoselectivity of the 18F-introduction, which is based on simple isotopic exchange, allows for a facile cartridge-based purification fully devoid of HPLC implementation, thereby yielding peptides with specific activities between 44.4 and 62.9 GBq μmol−1 (1,200-1,700 Ci mmol−1) within 25 min.
Im Titel ist 18 hochgestellt
Korrigierte Version: 23.10.2012, Korrektur betrifft Schreibweise der Autorin Katy Orchowski
Gesehen am 09.07.2018